New product development in small and medium-sized technology based companies: a multiple case study - Salgado, Eduardo Gomes; Salomon, Valério Antonio Pamplona; Mello, Carlos Henrique Pereira; Silva, Carlos Eduardo Sanches da (Acta Scientiarum. Technology, 2018)
The new product development (NPD) becomes more and more critical for the competitiveness, due to increasing internationalization of markets and diversification of products and decreasing life cycle of products. This paper addresses gaps in NPD literature, presenting a multiple case study involving small and medium-sized enterprises (SMEs), all of them are technology-based companies (TBC) manufacturers of electronics. A detailed investigation was conducted and three main sources of data were used for each case: documents from companies, in-depth interviews with NPD managers, and real-time observations. The different data sources enhanced reliability and validity to results. Our main finding is the identification of characteristics (e.g. Investment, establishing date, ISO 9001 certification) which influence these NPD in SMEs TBCs. Â